Comparison of the fecal microbiota of adult healthy dogs fed a plant-based (vegan) or an animal-based diet - Liversidge, Brooklynn D.; Gomez, Diego E.; Dodd, Sarah A. S.; MacNicol, Jennifer L.; Adolphe, Jennifer L.; Blois, Shauna L.; Verbrugghe, Adronie (Frontiers in Microbiology, 2024)
Purpose: Pet guardians are increasingly seeking vegan dog foods. However, research on the impact of these diets on gastrointestinal (GI) physiology and health is limited. In humans, vegan diets modify the GI microbiota, increasing beneficial digestive microorganisms. This study aimed to examine the canine fecal microbiota in response to a vegan diet compared to an animal-based diet. Methods: Sixty-one client-owned healthy adult dogs completed a randomized, double-blinded longitudinal study. Dogs were randomly assigned into two groups that were fed either a commercial extruded animal-based diet (MEAT, n = 30) or an experimental extruded vegan diet (PLANT, n = 31) for 12 weeks. Fecal collections occurred at the start of the experimental period and after 3-months of exclusively feeding either diet. Bacterial DNA was extracted from the feces, and the V4 region of the 16s rRNA gene was amplified using PCR and sequenced on Illumina MiSeq. Beta-diversity was measured using Jaccard and Bray-Curtis distances, and the PERMANOVA was used to assess for differences in fecal microbiota within and between groups. Alpha-diversity indices for richness, evenness, and diversity, as well as relative abundance, were calculated and compared between groups. Results: Beta-diversity differences occurred between diet groups at exit time-point with differences on Bray-Curtis distances at the family and genus levels (p = 0.007 and 0.001, respectively), and for the Jaccard distance at the family and genus level (p = 0.006 and p = 0.011, respectively). Significant differences in alpha-diversity occurred when comparing the PLANT to the MEAT group at the exit time-point with the PLANT group having a lower evenness (p = 0.012), but no significant differences in richness (p = 0.188), or diversity (p = 0.06). At exit-timepoint, compared to the MEAT group, the relative abundance of Fusobacterium, Bacteroides, and Campylobacter was lower in the PLANT group. The relative abundance of Fusobacterium decreased over time in the PLANT group, while no change was observed in the MEAT group. Conclusion: These results indicate that vegan diets may change the canine gut microbiota. Future studies are warranted to confirm our results and determine long-term effects of vegan diets on the canine gut microbiome.